Advertisements
Advertisements
Question
\[\lim_{x \to - \infty} \left( \sqrt{4 x^2 - 7x} + 2x \right)\]
Solution 1
\[\lim_{x \to - \infty} \left( \sqrt{4 x^2 - 7x} + 2x \right)\]
Let x =\[-\] m When n → – ∞, then m → ∞.
\[ = \lim_{m \to \infty} \left[ \left( \sqrt{4 m^2 = 7m} - 2m \right) \times \frac{\left( \sqrt{4 m^2 + 7m} + 2m \right)}{\left( \sqrt{4 m^2 + 7m} + 2m \right)} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{\left( 4 m^2 + 7m \right) - \left( 2m \right)^2}{\sqrt{4 m^2 + 7m} + 2m} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{4 m^2 + 7m - 4 m^2}{\sqrt{4 m^2 + 7m} + 2m} \right]\]
Dividing the numerator and the denominator by m:
\[\lim_{m \to \infty} \left[ \frac{7}{\sqrt{\frac{4 m^2 + 7m}{m^2}} + \frac{2m}{m}} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{7}{\sqrt{\frac{4 m^2}{m^2} + \frac{7m}{m^2}} + 2} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{7}{\sqrt{4 + \frac{7}{m}} + 2} \right]\]
\[\text{ As } m \to \infty , \frac{1}{m} \to 0\]
\[ = \frac{7}{\sqrt{4} + 2}\]
\[ = \frac{7}{4}\]
Solution 2
\[\lim_{x \to - \infty} \left( \sqrt{4 x^2 - 7x} + 2x \right)\]
Let x =\[-\] m When n → – ∞, then m → ∞.
\[ = \lim_{m \to \infty} \left[ \left( \sqrt{4 m^2 = 7m} - 2m \right) \times \frac{\left( \sqrt{4 m^2 + 7m} + 2m \right)}{\left( \sqrt{4 m^2 + 7m} + 2m \right)} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{\left( 4 m^2 + 7m \right) - \left( 2m \right)^2}{\sqrt{4 m^2 + 7m} + 2m} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{4 m^2 + 7m - 4 m^2}{\sqrt{4 m^2 + 7m} + 2m} \right]\]
Dividing the numerator and the denominator by m:
\[\lim_{m \to \infty} \left[ \frac{7}{\sqrt{\frac{4 m^2 + 7m}{m^2}} + \frac{2m}{m}} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{7}{\sqrt{\frac{4 m^2}{m^2} + \frac{7m}{m^2}} + 2} \right]\]
\[ = \lim_{m \to \infty} \left[ \frac{7}{\sqrt{4 + \frac{7}{m}} + 2} \right]\]
\[\text{ As } m \to \infty , \frac{1}{m} \to 0\]
\[ = \frac{7}{\sqrt{4} + 2}\]
\[ = \frac{7}{4}\]
APPEARS IN
RELATED QUESTIONS
\[\lim_{x \to 1} \frac{x^2 + 1}{x + 1}\]
\[\lim_{x \to 3} \frac{x^2 - 9}{x + 2}\]
\[\lim_{x \to - 5} \frac{2 x^2 + 9x - 5}{x + 5}\]
\[\lim_{x \to 2} \frac{x^3 - 8}{x^2 - 4}\]
\[\lim_{x \to - 1/2} \frac{8 x^3 + 1}{2x + 1}\]
\[\lim_{x \to 2} \left( \frac{1}{x - 2} - \frac{2}{x^2 - 2x} \right)\]
\[\lim_{x \to 4} \frac{x^2 - 16}{\sqrt{x} - 2}\]
\[\lim_{x \to 1} \left( \frac{1}{x - 1} - \frac{2}{x^2 - 1} \right)\]
\[\lim_{x \to - 2} \frac{x^3 + x^2 + 4x + 12}{x^3 - 3x + 2}\]
\[\lim_{x \to a} \frac{x^{2/3} - a^{2/3}}{x^{3/4} - a^{3/4}}\]
\[\lim_{x \to \infty} \frac{5 x^3 - 6}{\sqrt{9 + 4 x^6}}\]
\[\lim_{n \to \infty} \left[ \frac{1^2 + 2^2 + . . . + n^2}{n^3} \right]\]
Show that \[\lim_{x \to \infty} \left( \sqrt{x^2 + x + 1} - x \right) \neq \lim_{x \to \infty} \left( \sqrt{x^2 + 1} - x \right)\]
\[\lim_{x \to 0} \frac{\tan^2 3x}{x^2}\]
\[\lim_{x \to 0} \frac{\sin x^2 \left( 1 - \cos x^2 \right)}{x^6}\]
\[\lim_{x \to 0} \frac{\sin^2 4 x^2}{x^4}\]
\[\lim_{x \to 0} \frac{\tan x - \sin x}{\sin 3x - 3 \sin x}\]
\[\lim_{x \to 0} \frac{\sin \left( a + x \right) + \sin \left( a - x \right) - 2 \sin a}{x \sin x}\]
\[\lim_{x \to 0} \frac{x^2 - \tan 2x}{\tan x}\]
\[\lim_{x \to 0} \frac{\cos 2x - 1}{\cos x - 1}\]
\[\lim_{x \to 0} \frac{ax + x \cos x}{b \sin x}\]
\[\lim_{x \to 0} \frac{\tan 2x - \sin 2x}{x^3}\]
Evaluate the following limit:
\[\lim_{x \to 0} \frac{\sin\left( \alpha + \beta \right)x + \sin\left( \alpha - \beta \right)x + \sin2\alpha x}{\cos^2 \beta x - \cos^2 \alpha x}\]
\[\lim_{x \to \frac{\pi}{3}} \frac{\sqrt{3} - \tan x}{\pi - 3x}\]
\[\lim_{x \to \frac{\pi}{4}} \frac{\sqrt{2} - \cos x - \sin x}{\left( \frac{\pi}{4} - x \right)^2}\]
\[\lim_{x \to a} \frac{\cos \sqrt{x} - \cos \sqrt{a}}{x - a}\]
\[\lim_{x \to \frac{\pi}{2}} \left( \frac{\pi}{2} - x \right) \tan x\]
\[\lim_{x \to \frac{\pi}{2}} \frac{\left( \frac{\pi}{2} - x \right) \sin x - 2 \cos x}{\left( \frac{\pi}{2} - x \right) + \cot x}\]
\[\lim_{x \to \frac{\pi}{4}} \frac{\cos x - \sin x}{\left( \frac{\pi}{4} - x \right) \left( \cos x + \sin x \right)}\]
Evaluate the following limit:
\[\lim_{x \to \pi} \frac{1 - \sin\frac{x}{2}}{\cos\frac{x}{2}\left( \cos\frac{x}{4} - \sin\frac{x}{4} \right)}\]
\[\lim_{x \to 0} \frac{\log \left( a + x \right) - \log a}{x}\]
\[\lim_{x \to 0} \left( \cos x + \sin x \right)^{1/x}\]
Write the value of \[\lim_{x \to 1^-} x - \left[ x \right] .\]
Write the value of \[\lim_{x \to 0} \frac{\sin x^\circ}{x} .\]
\[\lim_{x \to 0} \frac{8}{x^8}\left\{ 1 - \cos \frac{x^2}{2} - \cos \frac{x^2}{4} + \cos \frac{x^2}{2} \cos \frac{x^2}{4} \right\}\] is equal to
The value of \[\lim_{x \to 0} \frac{1 - \cos x + 2 \sin x - \sin^3 x - x^2 + 3 x^4}{\tan^3 x - 6 \sin^2 x + x - 5 x^3}\] is
The value of \[\lim_{x \to \infty} \frac{n!}{\left( n + 1 \right)! - n!}\]
The value of \[\lim_{n \to \infty} \left\{ \frac{1 + 2 + 3 + . . . + n}{n + 2} - \frac{n}{2} \right\}\]
Evaluate the following limits: `lim_(x -> "a")[((z + 2)^(3/2) - ("a" + 2)^(3/2))/(z - "a")]`